Introducing a Fusarium Wilt Risk Calculator Tool for Watermelon Growers in Florida - Matthew Cullen; Daniel Perondi; Clyde Fraisse; Nicholas Dufault (EDIS)
Fusarium wilt of watermelon, caused by the fungus Fusarium oxysporum f. sp. niveum, is a threat to watermelon production in Florida. While a number of management options are available, numerous factors influence which management strategies are feasible for growers. This new 4-page publication of the UF/IFAS Plant Pathology Department introduces a tool that calculates the estimated risk of Fusarium wilt based on potential management strategies and environmental factors. This tool is intended for use by watermelon growers in Florida and should be helpful in advising them on management decisions. Written by Matthew Cullen, Daniel Perondi, Clyde Fraisse, and Nicholas Dufault. https://edis.ifas.ufl.edu/pp364